Silk-Ovarioids: Establishment and characterization of human ovarian primary cells 3D-model system - Di Nisio, Valentina; Li, Tianyi; Xiao, Zhijie; Papaikonomou, Kiriaki; Damdimopoulos, Anastasios; Végvári, Ákos; Lebre, Filipa; Alfaro-Moreno, Ernesto; Pedersen, Mikael; Svingen, Terje; Zubarev, Roman; Acharya, Ganesh; et al. (Karolinska Institutet, 2025)
The samples in the dataset are connected to a study focusing on establishment of a long-term stable three-dimensional (3D) model of human primary ovarian cells for toxicological research. These samples are collected from patients undergoing elective abdominal surgery. The cortex and medulla were separated and dissociated into single-cell suspension using mechanical and enzymatic methods, followed by culture in 2D and 3D systems. In total 75 samples are included in the dataset (36 samples from cortex and 39 from medulla). Among these samples, 29 tissue samples were used as reference in the comparison of 2D culture vs tissue and 3D culture vs tissue. 16 samples from 2D culture were used as the reference in the comparison of 3D vs 2D. The rest 30 samples were from 3D culture (Silk-Ovarioid).

RNA extraction of tissues and 2D cultured cells was performed using RNeasy Mini Kit (Qiagen, Germany). Total RNA of Silk-Ovarioids samples was extracted using RNeasy Micro Kit (Qiagen, Germany). Only samples with RIN values > 9 were used for library preparation. Libraries were prepared using Illumina Stranded mRNA Prep Ligation protocol (Illumina, USA) using 10 ng RNA as input. Pooled libraries were sequenced on Illumina NovaSeq 6000 platform. Fastq files were mapped to human genome GRCh38 using STAR (version 2.7.10b). subread package (version 2.0.1) was used to align the bam files using featureCount function. After import the raw data matrix into Rstudio, technical replicates were collapsed using DESeq2 collapseReplicates function. GRCh38 (Homo_sapiens.GRCh38.108.chr.gtf) was used for mapping and alignment.

The dataset consists of 150 files in fastq format, compressed with GNUzip (gzip), one file in txt format and one file in xlsx format. The total size of the dataset is approximately 400 GB.

Proverna i datamängden är kopplade till en studie med fokus på etablering av en långsiktigt stabil tredimensionell (3D) modell av mänskliga primära ovarieceller för toxikologisk forskning. Dessa prover samlas in från patienter som genomgår elektiv bukkirurgi. Cortex och medulla separerades och dissocierades till encellssuspension med hjälp av mekaniska och enzymatiska metoder, följt av odling i 2D- och 3D-system. Totalt ingår 75 prover i datasetet (36 prover från cortex och 39 från medulla). Bland dessa prover användes 29 vävnadsprover som referens i jämförelsen av 2D-kultur vs vävnad och 3D-kultur vs vävnad. 16 prover från 2D-kultur användes som referens i jämförelsen av 3D vs 2D. De övriga 30 proverna var från 3D-kultur (Silk-Ovarioid).

RNA-extraktion av vävnader och 2D-odlade celler utfördes med användning av RNeasy Mini Kit (Qiagen, Tyskland). Totalt RNA från Silk-Ovarioids-prover extraherades med användning av RNeasy Micro Kit (Qiagen, Tyskland). Endast prover med RIN-värden > 9 användes för biblioteksberedning. Bibliotek bereddes med användning av Illumina Stranded mRNA Prep Ligation-protokoll (Illumina, USA) med användning av 10 ng RNA som input. Poolade bibliotek sekvenserades på Illumina NovaSeq 6000-plattformen. Fastq-filer kartlades till humant genom GRCh38 med hjälp av STAR (version 2.7.10b). subread-paketet (version 2.0.1) användes för att justera bam-filerna med featureCount-funktionen. Efter import av rådatamatrisen till Rstudio kollapsades tekniska replikat med hjälp av DESeq2 collapseReplicates-funktionen. GRCh38 (Homo_sapiens.GRCh38.108.chr.gtf) användes för kartläggning och inriktning.

Datasetet består av 150 filer i fastq-format, komprimerade med GNUzip (gzip), en fil i txt-format och en fil i xlsx-format. Datasetets totala storlek är ungefär 400 GB.
Silk-Ovarioids: Establishment and characterization of human ovarian primary cells 3D-model system
Keywords: FERTILITY (HUMAN); FRUKTSAMHET; Ovary; Äggstock; Toxicology; Toxikologi; Transcriptome; Transkriptom; Medical Genetics and Genomics; Medicinsk genetik och genomik; Gynaecology, Obstetrics and Reproductive Medicine; Gynekologi, obstetrik och reproduktionsmedicin; Nanotechnology for/in Life Science and Medicine; Nanotekniska livsvetenskaper och medicin